Hypertension in Mozambique: trends between 2005 and 2015 - Jessen, N. (2018)
OBJECTIVE: To assess the current prevalence, awareness, treatment and control of arterial hypertension in Mozambican population, including adolescents and young adults, and to appraise their trends over the past decade, for the 25-64 years old population. METHODS: A cross-sectional study of a representative sample of the population aged 15-64 years (n=2965) was conducted in 2014-2015, following the Stepwise Approach to Chronic Disease Risk Factor Surveillance. Data from a survey conducted in 2005 using the same methodological approach was used to assess trends in the age group of 25-64 years. RESULTS: The prevalence of hypertension increased significantly, from 33.1 to 38.9% (P=0.048), whereas awareness (2005 vs. 2014-2015: 14.8 vs. 14.5%, P=0.914) and treatment among the aware (2005 vs. 2014-2015: 51.9 vs. 50.1%, P=0.770) remained similar. Control among the treated increased (from 39.9 to 44.5%, P=0.587), although not significantly. Mean blood pressure values increased (SBP: from 132.1 to 134.6mmHg, P=0.089; DBP: from 78.2 to 82.5mmHg, P<0.001). Among participants aged 15-24 years, in 2014-2015 the prevalence of hypertension was 13.1% (95% confidence interval: 9.8-16.4). CONCLUSION: Our findings show that the prevalence of hypertension in Mozambique is among the highest in developing countries, both in adults and adolescents, portraying an ample margin for reduction of the morbidity and mortality burden because of high blood pressure.